2019
DOI: 10.1039/c9ob00123a
|View full text |Cite
|
Sign up to set email alerts
|

Control of conformation in α-helix mimicking aromatic oligoamide foldamers through interactions between adjacent side-chains

Abstract: Hydrogen-bonding interactions are used to bias the conformation of an aromatic oligoamide foldamer in favour of an α-helix mimicking syn conformer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…As they are not coupled to the conjugated system, incorporating directional interactions into side chains enables structural control that is orthogonal to the function of the main chain and broadly applicable for many classes of main chain structures. Analogous to the design in Chart , our group’s previous work has demonstrated side chain engineering for guiding optical and responsive properties in phenylene-ethynylenes (PEs) via electron-poor fluoroarene pendants that cofacially stack with arenes in the PE chromophore (ArF–ArH interactions). This robust aromatic stacking interaction is useful in a variety of contexts to direct molecular packing. To accommodate these interactions, the PE linkages twist out of coplanarity by at least 55°, reducing conjugation. In addition, these ArF–ArH interactions insulate the PE chromophores from each other by blocking regions of overlap that are otherwise required for through-space coupling.…”
Section: Introductionmentioning
confidence: 99%
“…As they are not coupled to the conjugated system, incorporating directional interactions into side chains enables structural control that is orthogonal to the function of the main chain and broadly applicable for many classes of main chain structures. Analogous to the design in Chart , our group’s previous work has demonstrated side chain engineering for guiding optical and responsive properties in phenylene-ethynylenes (PEs) via electron-poor fluoroarene pendants that cofacially stack with arenes in the PE chromophore (ArF–ArH interactions). This robust aromatic stacking interaction is useful in a variety of contexts to direct molecular packing. To accommodate these interactions, the PE linkages twist out of coplanarity by at least 55°, reducing conjugation. In addition, these ArF–ArH interactions insulate the PE chromophores from each other by blocking regions of overlap that are otherwise required for through-space coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Our study on amide bond replacements encourages the application of these isosteres to replace not only other amides of albicidin or related cystobactamide structures 19−21 but also other peptide structures or aromatic oligoamides. 22,23 Whereas the (Z)-fluoroalkene ( 7) is a stateof-the-art well-known isostere, 24 to our knowledge, we report one of the very few examples 7 of an alkyne (5) considered to act as an amide isostere. 9 This Letter is a further important step in understanding the SARs of albicidin.…”
mentioning
confidence: 88%
“…These short sequences are structurally defined and have tunable sidechains. 29 Wilson demonstrated that these short oligomers could interact with large protein structures and can even restore catalytic function to an RNase (responsible for RNA degradation) (Fig. 13).…”
Section: Crescent and Helical Foldamers With Constrained Aromatic Oli...mentioning
confidence: 99%